Biodiesel production via homogeneous lewis acid catalyzed transesterification - Tio, Thiam Boon (2010)
The transesterification of triglyceride mostly found in vegetable oils with methanol using homogeneous lewis acid is one of promising method to convert triglyceride into fatty acid methyl ester which is an alternative to replace fossil fuel as energy source mostly in transportation industry.The present study investigated the use of Tin(II)Chloride,SnCl2 (Lewis acid catalyst) to catalyze the transesterification reaction of palm oil with methanol to fatty acid methyl ester(biodiesel)and the optimum conditions for biodiesel production.The conversion of palm oil to fatty acid methyl ester was analyzed by Gas Chromatography(GC).The analysis from Gas Chromatography showed that the conversion of triglycerides into fatty acid methyl esters using SnCl2 as catalyst was affected by catalyst concentration, methanol to oil molar ratio and temperature.The optimum conditions to afford 92.67 % conversion of palm oil to fatty acid methyl ester(biodiesel)is with the use of 18 to 1 methanol to oil molar ratio and reaction time of 240 minutes at 85 ºC in the presence of 7wt % Tin (II) Chloride as catalyst.